Seasonal and Spatial Growth Patterns of Shrimps Collected from Some Selected Creeks of Sindh, Pakistan - Faiza Sarwar; Jamil H. Kazmi (Journal of Basic & Applied Sciences, 2014)
Shrimps are very important part of the export economy of Pakistan. They share about 60 % the total exports of the sea food. For the studies of shrimp health, the length-weight studies are critical for the evaluation of the shrimp stocks. In this paper an attempt has been made to explore the Length-weight relationships of the shrimps at the creeks zone of Sindh coast (the study area). Furthermore, the impacts of seasonal change on the growth of shrimps (length and weight treated as parameter) have been evaluated. The main objective of this study is to analyze the seasonal and spatial pattern of growth and condition of the selected shrimp species. For this purpose, three most abundant shrimp species Penaeus indicus, Metapenaeus affinis and Exopalaemon styliferus have been selected out of 30 found at the coastal creeks areas of Sindh, Pakistan from April 2013 to January 2014. Pre and Post-Monsoon seasonal changes were analyzed through Geographic Information Science (GIS) and universally accepted equation for LWRs logW = alogLb were applied on three species selected. It has been found that post-monsoon is the ideal period for shrimp catch for three species. LWRs (growth pattern) found stable in Penaeus indicus and Metapenaeus affinis while predicting an alarming deteriorated situation for Exopalaemon styliferus at creeks zone.